Melone's Concept Revisited: 3D Quantification of Fragment Displacement - Teunis, Teun; Bosma, Niels H.; Lubberts, Bart; Ter Meulen, Dirk P.; Ring, David (Journal of Hand and Microsurgery, 2016)
We applied quantitative 3D computed tomography to 50 complete articular AO type C fractures of the distal radius and tested the null hypothesis that fracture fragments can be divided according to Melone's concept (radial styloid and volar and dorsal lunate facet fragments) and that each fragment has similar (1) displacement and (2) articular surface area. Thirty-eight fractures fit the Melone distribution of fragments. Radial styloid fragments were most displaced, and volar lunate fragments were least displaced. Volar lunate fragments had the largest articular surface area. While these findings confirm Melone's concepts, the finding that volar lunate fragments are relatively large and dorsal lunate fragments relatively small suggests that alignment of the volar lunate fragment with the radial styloid may be the key element of treatment and the dorsal lunate fragment may not routinely benefit from specific reduction and fixation.
Keywords: computed tomography; distal radius; fractures; morphology; quantitative